3D-Printed Drug/Cell Carrier Enabling Effective Release of Cyclosporin a for Xenogeneic Cell-Based Therapy. Issue 12 (December 2015) - Song, Tae-Ha; Jang, Jinah; Choi, Yeong-Jin; Shim, Jin-Hyung; Cho, Dong-Woo
Systemic administration of the immunosuppressive drug cyclosporin A (CsA) is frequently associated with a number of side effects; therefore, sometimes it cannot be applied in sufficient dosage after allogeneic or xenogeneic cell transplantation. Local delivery is a possible solution to this problem. We used 3D printing to develop a CsA-loaded 3D drug carrier for the purpose of local and sustained delivery of CsA. The carrier is a hybrid of CsA-poly(lactic- co -glycolic acid) (PLGA) microsphere-loaded hydrogel and a polymeric framework so that external force can be endured under physiological conditions. The expression of cytokines, which are secreted by spleen cells activated by Con A, and which are related to immune rejection, was significantly decreased in vitro by the released CsA from the drug carrier. Drug carriers seeded with xenogeneic cells (human lung fibroblast) were subcutaneously implanted into the BALB/c mouse. As a result, T-cell-mediated rejection was also significantly suppressed for 4 weeks. These results show that the developed 3D drug carrier can be used as an effective xenogeneic cell delivery system with controllable immunosuppressive drugs for cell-based therapy.